MULTI-HOP RELAY SELECTION FOR COOPERATIVE SENSING IN COGNITIVE RADIO NETWORKS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Spectrum sensing is one of the essential blocks of the cognitive radio (CR) system. Cooperative spectrum sensing (CSS) enhances sensing performance by exchanging information among secondary users (SUs). The paper addresses a situation where some SUs cannot communicate their local information with the fusion center (FC) due to real-time circumstances, i.e., shadowing, large distances, increased signal interference, etc. The issue can be resolved by introducing relay nodes to assist such SUs in transmitting local information to the corresponding destination (FC), making relay selection an essential component on which the system's performance depends. This paper proposes a critical path method (CPM) based multi-hop relay selection technique to select a set of relay nodes combined to form a relay with minimum path loss. The performance of the proposed scheme is compared with that of the existing methodologies to demonstrate its robustness and efficiency in terms of end-to-end path loss and reliability. In addition, a closed-form expression of outage probability is also developed to withstand the results.
Keywords: Cognitive Radio; Cooperative Sensing; Critical Path Method; Multi-hop Relay Selection; Universal software radio peripheral (USRP)